Fibromyalgia syndrome: the pharmacological treatment options - A. Marsico; R. Gorla; G. Leardini; R. Casale; F. Salaffi; S. Stisi; M. Di Franco; M. Cazzola; L. Bazzichi; M.A. Giamberardino; R.H. Gracely; D. Buskila; et al. (PAGEPress Publications, 2011)
Fibromyalgia (FM), also known as fibromyalgia syndrome (FMS), is a frequently observed systemic disorder characterized by widespread musculoskeletal pain (1, 2). Its prevalence in the general population is 1-3%, and it is more common among females than males. The American College of Rheumatology (ACR) classification criteria defines it as widespread pain with patients endorsing at least 11 of 18 tender points as painful (3). Although its defining feature is chronic, widespread pain, FM patients may also have a number of other symptoms including sleep disturbance, fatigue, irritable bowel syndrome, headache and mood disorders (1)....